PHYTOCHEMICAL CONSTITUENTS ANALYSIS OF ETHANOLIC EXTRACT OF MUSA PARADISIACA L. FLOWER USING GC-MS AND LC-MS - 1Mousa, K.A, Samsudin, N.I.P1,3, 1,2Abas, F and *1,2Rukayadi, Y., (Chelonian Research Foundation, 2023)
The investigation of natural sources for bioactive compounds with potential therapeutic applications has gained significant attention in recent years. Banana, or Musa paradisiaca L., is highly regarded for its nutritional content as well as for the variety of phytochemical components that contribute to its therapeutic benefits. This study aimed to analyze the phytochemical constituents of the ethanolic extract from M. paradisiaca flowers, with a focus on identifying bioactive compounds containing antimicrobial activities. The complex chemical composition of the ethanolic extract of M. paradisiaca flowers has been determined by analyses using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS). The GC-MS analysis was conducted using the QP2010 Ultra gas chromatography-mass spectrometer, coupled with a BP5MS column to facilitate precise separation of compounds. For LC-MS analysis, the Agilent 1290 Infinity LC system, coupled with the Agilent 6520 Accurate-Mass Q-TOF mass spectrometer featuring dual electrospray ionization (ESI) modes, was employed. The GC-MS analysis results showed that the ethanolic extract contains a variety of bioactive compounds, including hexadecenoic acid, 1-heptacosanol, 1-heneicosanol, 17-Pentatriacontene, diacetone alcohol, diisooctyl phthalate, fucosterol, heptadecanol, octadecane, octadecanoic acid methyl ester, phenol, 2,4-bis(1,1-dimethylethyl)-, squalene, and triacontane. Additionally, the LC-MS analysis identifies new bioactive compounds from M. paradisiaca flower ethanolic extract, such as hippeastrine, L-(-)-carvone, 4-hydroxybenzaldehyde, and vanillin. These compounds are believed to have antimicrobial properties, which is consistent with what has been found in extracts from other plants in previous studies. Thus, this study contributes to the understanding of the phytochemical composition of the ethanolic extract from M. paradisiaca flowers, which can be used for further exploration and applications in the fields of medicine and natural product-based antimicrobial approaches.